Study on colloidal synthesis of ZnS nanospheres embedded in reduced graphene oxide materials for sodium-ion batteries and energy storage mechanism - Jin, Youngho; Seong, Honggyu; Ha Moon, Joon; Lee, So Yi; Kim, Sung Kuk; Yang, MinHo; Lee, Jin Bae; Cho, Se Youn; Choi, Jaewon (Elsevier BV, 2023)
With growing demands for large-scale energy storage, metal sulfides have received great attention due to their high theoretical capacity as anode materials for sodium-ion batteries (SIBs). However, metal sulfides have a problem of poor stability. Thus, it is important to find suitable solutions. In this work, uniform ZnS nanospheres (ZnS NSs) are synthesized through a wet chemical method. And then, by compounding with reduced graphene oxide (rGO), ZnS NSs@rGO are synthesized in which ZnS NSs are evenly distributed on rGO. When we evaluate the cycle performance, ZnS NSs@rGO deliver a high discharge capacity of 634.6 mA h g-1 at a current density of 0.5 Ag-1 after 1000 cycles. Through charge/discharge processes of in-situ XRD analysis, we confirm the sodiation/desodiation mechanism of ZnS NSs@rGO.(c) 2023 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).